2019
DOI: 10.3390/nu11030669
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drugs and Excipients on Hydration Status

Abstract: Despite being the most essential nutrient, water is commonly forgotten in the fields of pharmacy and nutrition. Hydration status is determined by water balance (the difference between water input and output). Hypohydration or negative water balance is affected by numerous factors, either internal (i.e., a lack of thirst sensation) or external (e.g., polypharmacy or chronic consumption of certain drugs). However, to date, research on the interaction between hydration status and drugs/excipients has been scarce.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 182 publications
(244 reference statements)
0
29
1
1
Order By: Relevance
“…We employed captopril, a pharmacological compound routinely used for treating HT, as the positive control for the inhibitory activity against ACE. Although the effect of captopril has been reported to vary depending on its method of synthesis and interaction of its excipients [ 27 , 28 , 29 ], captopril IC50 values in our experimental conditions were observed to be in the ranges reported in the literature for this compound (0.021–0.58 μM). The results obtained from the inhibitory effect of ACE, both with captopril and EESH, permitted us to define the adequate concentrations to be used in the in vivo assays, i.e., BP control and gene expression assays.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…We employed captopril, a pharmacological compound routinely used for treating HT, as the positive control for the inhibitory activity against ACE. Although the effect of captopril has been reported to vary depending on its method of synthesis and interaction of its excipients [ 27 , 28 , 29 ], captopril IC50 values in our experimental conditions were observed to be in the ranges reported in the literature for this compound (0.021–0.58 μM). The results obtained from the inhibitory effect of ACE, both with captopril and EESH, permitted us to define the adequate concentrations to be used in the in vivo assays, i.e., BP control and gene expression assays.…”
Section: Discussioncontrasting
confidence: 45%
“…For example, Steinkamp-Fenske et al [ 21 ] and Zhou et al [ 32 ] analyzed the effect of administration of S. milthiorriza extracts on the regulation and production of NO in a human umbilical endothelium-derived cell line. The authors found a concentration-dependent response besides an over-regulation of eNOS in the treated cells, as compared to control cells [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. We analyzed genes coding for proteins that participate in three different pathways involved in regulation of HT, namely renin–angiotensin system ( Ace and Agtr1a genes), the kallikrein–kinin system ( Bdkrb2 gene) and the nitric oxide ( Nos3 gene) synthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs frequently consumed by the elderly (including antihypertensives, hypolipemic, hypoglycemics or drugs for acid- or nervous-related disorders) may trigger hypohydration by means of increased water elimination (through diarrhea, urine or sweat); decreased thirst sensation or appetite or alteration of central thermoregulation. On the other hand, excipients induce alterations in hydration status by decreasing gastrointestinal transit time or increasing the gastrointestinal tract rate or intestinal permeability [ 47 ].…”
Section: Polypharmacotherapymentioning
confidence: 99%
“…All these drugs have been linked to hyponatremia from non-osmotic AVP secretion, but their relationship to polydipsia is under-appreciated. Of note, a variety of drugs and excipients have been shown to affect hydration status by augmenting fluid losses, affecting thirst and/or appetite, increasing intestinal permeability and/or renal reabsorption rates [7].…”
Section: Psychologymentioning
confidence: 99%
“…For example, the clinical definition of dehydration is cellular dehydration from extracellular hypertonicity [5,6] while scientists often use the term dehydration to describe the process of losing water [4]. Alternatively, the term hypohydration refers to a negative water balance [7] or state of water deficit [4]. Regardless of which hydration terminology is utilized to define HS, the vast majority of the scientific and lay literature highlights the well-recognized detrimental effects of dehydration and/or hypohydration on a variety of conditions such as kidney stones [3], obesity [8], recurrent urinary tract infections [9], cognition [10], and athletic performance [11].…”
Section: Introductionmentioning
confidence: 99%